On Alawization in Syria - da Silva, Gabriela Santos (2021)
This paper employs the term ‘Alawization’ to define the prominence of members of the Alawi community in positions of power across Syria, a process that has already been noticed by some scholars, but that has not been named until now. We intend to answer the following questions: is there a process that can be called Alawization happening in Syria? How could Alawization have become a political process in the country? How could this have evolved over time? And how is it perceived among practitioners of international relations? Essentially, the circumstances that could allow for this process to take place are embedded in Syria’s colonial period and its evolution is closely related to the rise of Hafiz al-Assad to power – launching an “Assad dynasty”, that continues ruling the country. Perception of this ongoing process was based, methodologically, on historical representations and was investigated through semi-structured interviews with diplomats based at the UN working with Middle Eastern issues and/or that have already been assigned to posts in Syria. It concludes by suggesting that, albeit there’s recognition of this process, there is still disagreement on how it occurs and how widespread it is internally.